Kamenev and Philos-types oscillation criteria for fourth-order neutral differential equations - Omar Bazighifan (Advances in Difference Equations, 2020)
Abstract This work is concerned with the oscillatory behavior of solutions of fourth-order neutral differential equations. By using the Riccati transformation and integral averaging techniques we obtain some new Kamenev-type and Philos-type oscillation criteria. Our results extend and improve some known results in the literature. An example is given to illustrate our main results.